2017
DOI: 10.1001/jama.2017.17225
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Self-reported and Biochemically Tested Marijuana Use Among Pregnant Females in California From 2009-2016

Abstract: Marijuana is the most commonly used illicit drug during pregnancy, and its use is increasing. From 2002 to 2014, the prevalence of self-reported, past-month marijuana use among US adult pregnant women increased from 2.4% to 3.9%. 1 In aggregated 2002-2012 data, 14.6% of US pregnant adolescents reported past-month use. 2 However, studies are limited to self-reported surveys and likely underestimate use due to social desirability bias and underreporting, leaving the scope of the problem unclear. We investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
198
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(210 citation statements)
references
References 5 publications
8
198
1
3
Order By: Relevance
“…Overall, the prevalence of prenatal cannabis use ranged from 0.24% to 22.6% across studies (Table S1). Prenatal cannabis users tended to be younger than 25 years of age, single, and of low parity, compared with nonusers. They were also more likely to have lower income, less than a high school education, and public or no health insurance .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Overall, the prevalence of prenatal cannabis use ranged from 0.24% to 22.6% across studies (Table S1). Prenatal cannabis users tended to be younger than 25 years of age, single, and of low parity, compared with nonusers. They were also more likely to have lower income, less than a high school education, and public or no health insurance .…”
Section: Resultsmentioning
confidence: 94%
“…After duplicates were removed, 6542 publications were screened by title and abstract. Of these, 109 were retrieved for full‐text review and 41 studies were included in our scoping review …”
Section: Resultsmentioning
confidence: 99%
“…Another study found a relatively similar increase from 4.2% in 2009 to 7.1% in 2014 2 . Corresponding rates of alcohol use (e.g., 2001–2005:11.2% vs. 2011–2013:10.2%) and cigarette smoking (e.g., 2002: 13.3% vs. 2010: 12.3%) during pregnancy have generally decreased 3,4,5 .…”
Section: Introductionmentioning
confidence: 77%
“…In a recent national survey of the prevalence and patterns of substance use among pregnant women, 2.8% reported marijuana use during their first trimester of pregnancy (Sobrian, ). A recent study has reported that about 20% of pregnant women 24 years and younger tested positive for marijuana use (Young‐Wolff et al, ).…”
Section: Introductionmentioning
confidence: 99%